Juvenile xanthogranuloma: unusual intraoral finding. Issue 1 (January 2015) - Collins, L.; Banks, R.; Robinson, M.
Abstract Juvenile xanthogranuloma is a rare non-Langerhans cell histiocytosis that usually presents as a self-limiting dermatological condition in young children. Rarely, extracutaneous sites may also be involved. We report a case in a 3-year-old girl that presented intraorally as a solitary, well-defined, soft, purple palatal swelling. Patients with these rare intraoral lesions may present to dentists and subsequently to oral and maxillofacial surgeons. Diagnosis requires histopathological analysis and immunohistochemical staining. Further investigation from other specialties is required to rule out involvement of other organ systems.